PENGGUNAAN MODEL PEMBELAJARAN EXAMPLE NON EXAMPLE UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA TUNAGRAHITA KELAS VII - Zeni Abidah; Ahmad Samawi (Jurnal ORTOPEDAGOGIA, 2014)
The purposes of this research are to Describe: 1) the process of learning in improving students with Intellectual Disabilityscience achievement of clasifying animals based on the kind of food using Example non Example learning model, 2) Student with Intellectual Disabilityscience achievement of clasifying animals based on the kind of food using Example non Example learning model.The result of this research showed that: 1) The using of Example non Example learning model consiting of preparing of learning tools, showing animal pictures, students discussion, group presentation and conclusion, 2) The result of the study showed the students achievement is improved, approximately 43,33% in pre activity with complete learning at 16,66% to be 68,33% with coplete learning at 33,34% in the first cycle and then improved approximately 90,00% with classically coplete learning 83,34% in the second cycle. Penelitian ini bertujuan 1) Mendeskripsikan proses pembelajaran dalam meningkatkan hasil belajar IPA pada siswa tunagrahita dengan menggunakan model pembelajaran Example non Example, 2) Mendeskripsikan peningkatan hasil belajar IPApada siswa tunagrahita dengan model pembelajaran Example non Example.Hasil penelitian ini menunjukkan bahwa 1) Penggunaanmodel pembelajaran Example non Exampleyang meliputi persiapan perangkat pembelajaran, menampilkan gambar-gambar hewan, diskusi siswa, presentasi kelompok dan kesimpulan, 2) Hasil penelitian menunjukkan hasil belajar siswa meningkat, pada prakegiatan rata-rata mencapai 43,33% dengan ketuntasan belajar sebesar 16,66% menjadi 68,33% dengan ketuntasan belajar sebesar 33,34% pada siklus I dan meningkat rata-ratanya menjadi90,00% dengan ketuntasan belajar klasikal sebesar 83,34% pada siklus II.